BLOCKCHAIN ZAKAT IN LAW PERSPECTIVE AND ITS IMPLICATION ON ZAKAT MANAGEMENT - Yusuf, Muhammad Zulfikar; Aufa, Muhammad Fikri; Umam, Khotibul (istinbath, 2024)
The main aim of distributing zakat is to provide the broadest possible benefits to those in need whose basic needs, such as clothing, food, and shelter, are not yet met. One effort that can be used to optimize the management and distribution of zakat funds is using blockchain technology. This research is a qualitative descriptive with library research. The method used in this research is a normative legal research methodology with a conceptual approach based on the theories of Economic Analysis of Law and Theory of Change. This research shows that Islamic and normative laws provide opportunities to develop blockchain zakat while prioritizing effective and efficient Sharia principles and legal principles. If applied to zakat institutions, blockchain has various positive impacts, especially in managing zakat funds. Some of the positive effects of using blockchain technology include transparency and accountability, systematic fund tracking, smart contracts with automation methods, efficient administration costs, encrypted security features, cross-border network access, and others. These various advantages will undoubtedly impact increasing public trust in zakat institutions, thereby optimizing the potential of zakat funds and producing a much more significant contribution to the distribution and utilization of zakat funds to mustahik and the wider community.